¿Debe tenerse en cuenta la capacidad económica del sujeto obligado en la tipicidad del delito de omisión a la asistencia familiar? - Vinelli Vereau, Renzo Antonio (2019)
In this paper, the authors discuss the maintenance obligation recognized by Peruvian civil laws, which the civil judge analyzes taking into account the economic capacity of the debtor. On the other hand, the Peruvian law typifies the crime of omission of family assistance, which is verified by the sole breach of the obligation by the debtor. However, criminal jurisprudence has not taken into account the concept of economic capacity as an objective element of this offence, unlike their civil counterpart. Thus, the authors discuss the need to include the economic capacity of the debtor in the analysis of the crime of omission of family assistance.